Evaluation of the metabolic status and sarcopenia in the long-term period after Roux-en-Y gastric bypass and mini-gastric bypass surgery - A. G. Khitaryan; B. B. Khatsiev; A. V. Mezhunts; A. V. Sarkisyan; D. A. Melnikov; A. A. Orekhov; S. A. Adizov; A. A. Abovyan; S. P. Makarevich; S. S. Burtcev (Вестник хирургии имени И.И. Грекова, 2021)
INTRODUCTION. Bariatric operations lead to changes in body composition. The desired fat loss may be accompanied by decrease of muscle mass, thus raising the risk of sarcopenia.The OBJECTIVE was to evaluate the long-term results of surgical treatment of morbid obesity and concomitant comorbid conditions, as well as a decrease of muscle mass in the pre - and long-term postoperative period.METHODS AND MATERIALS. This prospective randomized controlled blind trial included the results of treatment of 241 patients. Patients were divided into 2 groups depending on the type of surgical treatment. The first group consisted of 116 people who underwent RYGB; the second group included 125 patients who underwent OAGB/MGB. 83 patients from the first group and 95 patients from the control group at the preoperative stage and 24 months after the operation randomly underwent bioelectrical impedance with the determination of skeletal muscle mass (SMM) and skeletal muscle mass index (SMMI)=SMM/Height2. The calculated SMMI index for men normally corresponds to >10.76 kg/m2; moderate sarcopenia SMMI=8.51–10.75 kg/m2; the SMMI index of ≤8.5 kg/m2 corresponds to severe sarcopenia. For women, this index is normally ≥6.76 kg/m2; moderate – 5.76–6.75 kg/m2; severe sarcopenia ≤5.75 kg/m2. Bioelectrical impedance were performed on a «AVS-01 Medass» bioelectrical impedance body composition analyzer (Russia). RESULTS. The difference in changes in the results of anthropometric indicators, as well as laboratory indicators of diabetes compensation within 24 months in both groups was statistically insignificant (p>0.05). According to bioelectrical impedance data, the incidence of sarcopenia in patient groups was as follows: the initially normal ratio of muscle mass to the square of growth in meters, i.e. normal SMMI in 71 (85.5 %) patients in the group with RYGB, and in 78 (85.7 %) patients in the group with OAGB/MGB. Moderate sarcopenia was detected in 12 (14.5 %) patients with RYGB and 13 (14.3 %) patients with OAGB/MGB. 24 months after the operation, SMMI was distributed as follows – Norm in 59 (71.1 %) patients of the study group and 47 (51.6 %) patients in the control group. Moderate sarcopenia was found in 16 (19.3 %) patients in the group of patients with RYGB, and in 29 (31.9 %) cases in the group of patients with OAGB/MGB. Severe sarcopenia was observed in 8 (9.6 %) patients of the first group and 15 (16.5 %) patients of the second group (p=0.0001).CONCLUSIONS. Bariatric bypass surgery results in significant changes in body composition 24 months after surgery. Bioelectrical impedance allows to effectively detect these changes. The desired weight loss is associated with a significant decrease in skeletal muscle mass, mineral mass. Thus, patients after bypass surgery are at risk of sarcopenia. Sarcopenia is more pronounced in patients after OAGB/MGB than after RYGB.